Evaluasi Tingkat Kapabilitas Sumber Daya Teknologi Informasi Pada Institut Teknologi Nasional Malang Menggunakan Kerangka Kerja Cobit 5 - Sihombing Nella Sarah Berlianna; Suprapto suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
IT is the main component of business that produce many advantages for an enterprise. When an enterprise is implementing IT, they have to manage it in the right way so that the utilization can fulfill the needs. ITN Malang is one of the education institute that implement IT in case of business. However, based on the interview information, in reality there are few obstacles that happen in the management of their technology resource. One of the solution that ITN Malang can take is to evaluate the capability level of their technology resource using COBIT 5. COBIT 5 is a framework that can help an enterprise produce the optimal value of the IT utilization in a way of balancing between advantage and risk. The domain of COBIT 5 that used to evaluate the capability level of IT resource are EDM04 Ensure Resource Optimisation, AP007 Manage Human Resource, BAI09 Manage Assets, and DSS01 Manage Operations. The result shows that the capability level of information techonology resource of ITN Malang is at level 1 performed process with the gap value that obtained is 1. To reach out to level 2 which is manage process, ITN Malang should make asset and human resource planning.